The role of pharmacists in mitigating medication errors in the perioperative setting: a systematic review - Lina Naseralallah; Somaya Koraysh; May Alasmar; Bodoor Aboujabal (Systematic Reviews)
Abstract Introduction Medication errors occur at any point of the medication management process and are a major cause of death and harm globally. The perioperative environment introduces challenges in identifying medication errors due to the frequent use of time-sensitive, high-alert medications in a dynamic and intricate setting. Pharmacists could potentially reduce the occurrence of these errors because of their training and expertise. Aim To provide the most up-to-date evidence on the roles and effects of pharmacist interventions on medication errors in perioperative settings. Methods PubMed, CINAHL, and Embase were searched from inception to September 2023. Studies were included if they tested a pharmacist-led intervention aimed at reducing medication errors in adult perioperative settings. The included studies were assessed for quality using the Crowe Critical Appraisal Tool. Data were extracted and synthesized using the DEPICT-2 (Descriptive Elements of Pharmacist Intervention Characterization Tool). Screening, quality assessment, and data extraction were performed by two independent researchers. Results Sixteen studies were eligible. All included studies incorporated multicomponent interventions, primarily medication reconciliation (n = 13), medicine-related recommendations (n = 12), staff education (n = 6), and patient counselling (n = 4). The development of implemented interventions was poorly reported across all papers. A diverse range of error reporting was observed, and none of the included studies provided definitions or basis for the categorization of errors. Although the studies showed that pharmacist interventions were associated with a reduction in overall medication errors rates, some studies showed inconsistent findings regarding error subtypes. The most common pharmacist intervention was medication optimization via holding or switching between agents. Conclusion While there is some evidence of positive impact of the pharmacist-led interventions on medication errors in perioperative setting, this evidence is generally of low quality and insufficient volume. Heterogeneity in study design, definitions, and case detection is common; hence, high-quality research that applies more stringent controls and uses clearer definitions is warranted. Systematic review registration PROSPERO CRD42023460812.